FCC Matrix Components and Their Combination with Y Zeolite to Enhance the Deoxygenation of Bio-oils - Bertero, Melisa Paola (2021)
The immediate catalytic conversions of pyrolytic bio-oils from pine sawdust and soybean shell over mesoporous catalysts (silica, alumina, and silica-alumina) and their combinations with Y zeolite, were studied. The effect of mesoporosity and acidity on the bio-oil deoxygenation and conversion into hydrocarbons was investigated. Pyrolysis and immediate catalytic conversion of bio-oil were performed in an integrated pyrolysis–upgrading reactor, for 7 min under a 30-ml/min flow of nitrogen at 550 °C. Important differences were observed in the conversion of the bio-oils, according to the composition of the raw biomasses. Pine sawdust bio-oil produced more coke and less hydrocarbons in the range of gasoline than soybean shell bio-oil over all the catalysts. Mesoporous catalysts showed conversion and deoxygenation between 14 and 29 percentage points higher with the more acidic solid (SiO2-Al2O3) in the case of pine sawdust bio-oil and between 2 and 10 percentage points higher with the solid having the highest specific surface area (SiO2) in the case of soybean shell bio-oil. Among the compound catalysts, the best performance for the case of pine sawdust corresponded to the catalyst with the highest mesoporosity (Y/SiO2), while for soybean shell corresponded to the most acidic catalysts (Y/Al2O3 and Y/SiO2-Al2O3). Soybean shell bio-oil showed more low molecular weight compounds (less than 130 g mol−1), which diffuse more easily in the zeolite channels, thus favoring conversion and deoxygenation mechanisms. On the contrary, for pine sawdust bio-oil, the surface area contributed by the mesopores in the matrix played a key role in pre-cracking bulky molecules.